2012
DOI: 10.1177/0748730411429447
|View full text |Cite
|
Sign up to set email alerts
|

Forced Desynchronization of Activity Rhythms in a Model of Chronic Jet Lag in Mice

Abstract: We studied locomotor activity rhythms of C57/Bl6 mice under a chronic jet lag (CJL) protocol (ChrA(6/2) ), which consisted of 6-hour phase advances of the light-dark schedule (LD) every 2 days. Through periodogram analysis, we found 2 components of the activity rhythm: a short-period component (21.01 ± 0.04 h) that was entrained by the LD schedule and a long-period component (24.68 ± 0.26 h). We developed a mathematical model comprising 2 coupled circadian oscillators that was tested experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
63
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 37 publications
6
63
0
5
Order By: Relevance
“…Indeed, either a delay (c) or an advance (d) of the LD cycle will impose a delaying or advancing light-input to the clock, respectively, which will gradually entrain to the new conditions. Finally, chronic jet lag schedules (e, f) or T-cycles outside the entrainment range (g, h) (see Casiraghi et al 2012), are used in the laboratory to study the circadian system under extreme entraining conditions. While the clock can entrain to gradual changes in the LD cycle, when animals are subjected to frequent phase advances of the LD cycle, relative coordination and/or forced desynchronization of behavioral rhythms can be observed described as follows: (a) permanent: people work regularly on one shift only, i.e.…”
Section: Shift Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, either a delay (c) or an advance (d) of the LD cycle will impose a delaying or advancing light-input to the clock, respectively, which will gradually entrain to the new conditions. Finally, chronic jet lag schedules (e, f) or T-cycles outside the entrainment range (g, h) (see Casiraghi et al 2012), are used in the laboratory to study the circadian system under extreme entraining conditions. While the clock can entrain to gradual changes in the LD cycle, when animals are subjected to frequent phase advances of the LD cycle, relative coordination and/or forced desynchronization of behavioral rhythms can be observed described as follows: (a) permanent: people work regularly on one shift only, i.e.…”
Section: Shift Workmentioning
confidence: 99%
“…In addition, we have developed a chronic jet lag schedule consisting of a 6 h LD-advance each two days, which generated a stable desynchronization of two activity components in mice (Casiraghi et al 2012) and exerted severe metabolic alterations (unpublished results). Moreover, animals under similar chronic jet lag protocols showed biphasic corticosterone rhythms (Filipski et al 2004), attenuated AVP and Pk2 expression in the SCN (Yan 2011), and alterations in PER2 expression rhythms in the SCN, thymus, and liver (Castañon-Cervantes et al 2010).…”
Section: Simulated Jet Lagmentioning
confidence: 99%
“…It has been shown that entrainment of a free-running circadian oscillator occurs only for a specific range of period and light intensity combinations of the light/dark cycle which set the "range of entrainment" (Abraham et al, 2010;Casiraghi et al, 2012;Granada et al, 2011). In our "random pulse" paradigm, we have fixed the period of the For a fixed light intensity L of 1,000 lux, entrainment was lost after I was gradually increased to 20 hours, as predicted by our computer simulations (Flôres et al, 2013).…”
Section: 3)mentioning
confidence: 72%
“…Each day the light stimulus impinges a phase-shift on the oscillator, but the shift occurs only after transient slow changes in amplitude (Abraham et al, 2010;Casiraghi et al, 2012;Granada et al, 2011;Peterson, 1980). If the amplitude were instantly recovered our random pulse regimens would presumably cause equally random back and forth changes in the phase of the circadian oscillator, possibly failing to keep the phase stable within a 24-hour day.…”
Section: Discussionmentioning
confidence: 99%
“…Não somente em organismos fotossintetizantes, mas para qualquer modelo tal conceito é essencial, um exemplo são as análises do comportamento de camundongos em rodas de exercício que registram ao longo de meses a frequência da atividade dos animais submetidos a diversas condições. (CASIRAGHI et al, 2012;VALENTINUZZI et al, 2009), utilizando o menor esforço possível do observador.…”
Section: Ensaio Enzimático Da Nrunclassified